Gender Stereotypes in Student Evaluations of Teaching - Renström, Emma A.; Gustafsson Sendén, Marie; Lindqvist, Anna (Frontiers in Education, 2021)
This paper tests how gender stereotypes may result in biased student evaluations of teaching (SET). We thereby contribute to an ongoing discussion about the validity and use of SET in academia. According to social psychological theory, gender biases in SET may occur because of a lack of fit between gender stereotypes, and the professional roles individuals engage in. A lack of fit often leads to more negative evaluations. Given that the role as a lecturer is associated with masculinity, women might suffer from biased SET because gender stereotypes indicate that they do not fit with this role. In two 2 × 2 between groups online experiments (N’s = 400 and 452), participants read about a fictious woman or man lecturer, described in terms of stereotypically feminine or masculine behavior, and evaluated the lecturer on different SET outcomes. Results showed that women lecturers were not disfavored in general, but that described feminine or masculine behaviors led to gendered evaluations of the lecturer. The results were especially pronounced in Experiment 2 where a lecturer described as displaying feminine behaviors was expected to also be more approachable, was better liked and the students rather attended their course. However, a lecturer displaying masculine behaviors were instead perceived as being more competent, a better pedagogue and leader. Gender incongruent behavior was therefore not sanctioned by lower SET. The results still support that SET should not be used as sole indicators of pedagogic ability of a lecturer for promotion and hiring decisions because they may be gender-biased.